Sharon Osbourne extreme : my autobiography - Osbourne, Sharon; Dening, Penelope (New York : Springboard Press, 2006)
The author describes her extraordinary childhood as the daughter of infamous music manager Don Arden, managing and marrying rock legend Ozzy Osbourne, and her own rising fame on television shows such as "The Osbournes" and "The X- Factor."
Keywords: Osbourne, Sharon; Television personalities -- Great Britain -- Biography